Analysing Factor To Improve Data Quality In Integrated Operation System In Oil And Gas Industry At Xyz Organization - Hendradi Walujo (Syntax Corporation, 2022)
Back in 2012 Integrated Operating System known as SOT (Sistem Operasi Terpadu) was started to implement in order to conduct reporting Oil and Gas Production to all stakeholders such as related Government and Ministry, House of Representatives and Supervisory Agency. The program is always being improved to have better quality on both data, infrastructure, people and process to address some problem in regards with data completeness, accuracy and timeliness. In order to address the issue arises the study has been conducted to see the problem by discussing with multi parties, study of literatures and discuss the propose framework with SME’s. The well-known standard such as COBIT and DMM also support to mapping and having insight of the observed gaps. At the end this study come up with the plan of action on how the data quality is improved from many perspectives on how the policy and principle, culture and behavior, information and communication, skill of people and competencies, to management commitment and infrastructure.